Structural organization and thermal properties of the Sb2O3-SbPO4 glass system - Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Poulain, M.; Briois, V; Brunklaus, G.; Rosenhalm, C.; Mosel, B. D.; Eckert, H. (Royal Soc Chemistry, 2004)
The structural organization of Sb2O3-SbPO4 glasses has been studied by FTIR, Raman, P-31 MAS and spin echo NMR, Mossbauer and X-ray absorption spectroscopy (EXAFS and XANES at K and L-3,L-1-Sb edges). The combined results can be explained in terms of two potential mechanisms describing the change of the Sb(m) local environment upon incorporation of Q((4))-type phosphate. The formation of the latter species requires anionic compensation that may be adjusted by (a) formation of non bridging oxygen or (b) formation of SbO4E- groups (E = non-bonding electron pair). The second model is favored.